2010
DOI: 10.1002/jsfa.3919
|View full text |Cite
|
Sign up to set email alerts
|

The influence of small- and large-scale composting on the dissipation of pesticide residues in a biopurification matrix

Abstract: Industrial and small-scale composting/incubation reduced the concentration of some pesticides during the timeframe studied, although little reduction was obtained for the persistent pesticide bifenthrin in the industrial composting process and for linuron in barrel incubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…In general, the dissipation of pesticide residues in our study was similar or slightly lower than that recorded in the composting of exhausted biomixtures, although in those studies, other types of pesticides were analyzed and the biomixtures contained other organic substrates [6,7], which might explain the differences observed.…”
Section: Dissipation Of Pesticide Residues In the Biomixturessupporting
confidence: 69%
See 1 more Smart Citation
“…In general, the dissipation of pesticide residues in our study was similar or slightly lower than that recorded in the composting of exhausted biomixtures, although in those studies, other types of pesticides were analyzed and the biomixtures contained other organic substrates [6,7], which might explain the differences observed.…”
Section: Dissipation Of Pesticide Residues In the Biomixturessupporting
confidence: 69%
“…Therefore, decontamination of exhausted biomixtures is essential prior to their final disposal or prior to their possible reuse to enhance biodegradation in new biobeds [5]. Previous studies revealed that, after 76 days of composting and maturation, 70% of bentazon, 93% of linuron, 90% of metalaxyl and 20% of bifenthrin were dissipated from a contaminated biomixture used in a biopurification system [6]. Karas et al [7] showed that bioaugmentation with pesticides degrading bacteria removed 83% and 97% of thiabendazole and imazalil, respectively, Appl.…”
Section: Introductionmentioning
confidence: 99%
“…Composting applied either alone or in combination with bioaugmentation accelerated the dissipation of IMZ and TBZ respectively during the active composting phase. Previous studies by De Wilde et al [16] showed that composting resulted in 70% dissipation of bentazon and linuron by a spent biobed substrate. Composting contributes to the dissipation of pesticides via a range of processes with biodegradation being dominant [42].…”
Section: Discussionmentioning
confidence: 97%
“…This constitutes a key regulatory issue withholding the wider adoption of biobeds [14]. However only a few studies have addressed it [15,16].…”
Section: Discussionmentioning
confidence: 99%